2017
DOI: 10.2147/dddt.s143875
|View full text |Cite|
|
Sign up to set email alerts
|

Protective role of quercetin against manganese-induced injury in the liver, kidney, and lung; and hematological parameters in acute and subchronic rat models

Abstract: Manganese (Mn) is an important mineral element required in trace amounts for development of the human body, while over- or chronic-exposure can cause serious organ toxicity. The current study was designed to evaluate the protective role of quercetin (Qct) against Mn-induced toxicity in the liver, kidney, lung, and hematological parameters in acute and subchronic rat models. Male Sprague Dawley rats were divided into control, Mn (100 mg/kg for acute model and 15 mg/kg for subchronic model), and Mn + Qct (25 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Animal studies claim that under the circumstances where liver enzymes are increased, quercetin can effectively reduce AST, ALT, and ALP. [222324] Human interventional studies, on the other hand, reported various results. Moayedi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies claim that under the circumstances where liver enzymes are increased, quercetin can effectively reduce AST, ALT, and ALP. [222324] Human interventional studies, on the other hand, reported various results. Moayedi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Manganese (Mn) is an important mineral element required in trace amounts for development of the human body, while over‐ or chronic exposure can cause abnormal sympathovagal balance and serious organ toxicity . It has been implicated that the renal injury was possibly induced by the manganese accumulation in kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Spermine, the peculiar odorous chemical of semen, has been identified as a CaSR agonist . Clinically, increased exposure to manganese exposure, one of CaSR agonists, may cause central autonomic dysfunction and acute renal injuries by an undefined mechanism. Exacerbated activation of sympathetic nervous activity by bladder afferents induces a vesciovascular reflex mediated vasoconstriction in renal and hepatic vascular beds further, thereby contributing to oxidative injury and apoptosis in the kidney and liver .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some others reported beneficial effects of quercetin on RBC and hematocrit (39). The platelet rates' values were significantly increased with simultaneous quercetin administration and polychlorinated biphenyls (40) or acute and sub-chronic manganese administration (41). Some studies have shown an inhibition of platelet aggregation following supplementation with flavonoids in vivo (42,43).…”
Section: Hematologic and Biochemical Parametersmentioning
confidence: 99%